How can ecologists thrive during the global environmental crisis? Lessons from the ancient world. Issue 6 (7th November 2019) - Freeling, Benjamin S.; Preston, Tamas K.
Abstract : When striving to meet an immense challenge, how can we, as restoration ecologists, flourish? Given the ongoing environmental crisis, it is normal to experience ecological grief and discouragement. This article discusses how insights from the ancient philosophy of Stoicism can help environmental practitioners navigate these troubling times. To overcome ecological grief, ecologists can draw on three tenets from Stoic thought: distinguishing between what we can and cannot control; recognizing our contribution as part of a broader community of environmental managers; and focusing on the intent of our actions. We believe that these ideas can help ecologists shoulder the emotional burden of modern environmental practice and focus on working toward a diverse and resilient biosphere.